Konsistensi Orang Tua dalam Mengupayakan Pendidikan Karakter terhadap Anak di Desa Bejen, Karanganyar - Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti; Baidan, Nashruddin (Darul Yasin Al Sys, 2024)
Parents are the first and main education for their children, a child will grow and develop and have good character which can be seen in the parents' parenting style. Coaching or education that is carried out well will give birth to a generation that has good morals, so a balanced education is needed, namely education that pays attention to all aspects, namely the heart, mind and physique. The role of parents in seeking education is considered important because education is not a trivial matter because education is the main capital that every individual must have in order to survive in accordance with the times. With that, parents need to realize the importance of providing the best education for their children from early childhood education. Parental involvement. Parents' consistency in seeking character education for their children needs to be done in appropriate stages so that it can produce a generation that has noble character.